Efficacy of danhong injection adjuvant therapy in patients with acute ischemic stroke: a real-world, multicenter, retrospective study - Pan, Danping; Wan, Haitong; He, Yu; Yang, Jiehong; Guo, Yilei; Yu, Li; Zhang, Feihu; Zheng, Guoqing; Xu, Bin; Song, Yaohong; Zhao, Mingjun; Liu, Xiangzhe; et al. (Frontiers in Pharmacology, 2025)
BackgroundPrevious clinical and experimental studies indicate that Danhong injection (DHI) confers protective effects against acute ischemic stroke (AIS). However, due to limited sample sizes, large-scale clinical studies are still needed to confirm its efficacy.MethodsThis real-world, multicenter retrospective study used inpatient data from eight centers across Mainland China. AIS patients were divided into a DHI group or a Non-DHI group depending on whether they received DHI (7–14 consecutive days). Propensity score matching (PSM) was applied to balance baseline differences, and multiple analytical methods (crude analysis, multivariate regression, stabilized inverse probability of treatment weighting [sIPTW], and PSM combined with multivariate regression) were conducted. The primary outcome was the NIHSS score at discharge. Secondary outcomes included the proportions of patients with post-treatment NIHSS scores ≤4 or ≤1, the mRS score, the proportion of patients achieving mRS ≤1, and the incidence of in-hospital complications (IHC).ResultsA total of 3,560 patients were enrolled, including 1,425 in the DHI group, and 2,135 in the Non-DHI group, with 1,415 matched pairs identified via PSM. After treatment, the NIHSS score in the DHI group was 2.01 ± 3.10, compared with 2.50 ± 3.26 in the Non-DHI group, indicating significantly lower scores in the DHI group (adjusted RR = 0.81, 95% CI: 0.74–0.88, P < 0.001). These findings were consistent across multiple analytical methods (RR = 0.79–0.82). After treatment, the proportion of patients with NIHSS ≤4 and ≤1 was higher in the DHI group (adjusted RR = 1.02, 95% CI: 1.01–1.03, P = 0.005; adjusted RR = 1.07, 95% CI: 1.05–1.10, P < 0.001). The DHI group also had a lower mRS score (P < 0.001) and a higher proportion of patients achieving mRS ≤1 (adjusted RR = 1.12, 95% CI: 1.10–1.15, P < 0.001). No noteworthy difference was found between the two groups in the incidence of IHC (adjusted RR = 1.01, 95% CI: 0.99–1.03, P = 0.320).ConclusionDHI adjunctive therapy may improve neurological outcomes in patients with AIS. However, additional randomized controlled trials (RCTs) are needed to confirm its effectiveness in routine biomedicine-based clinical practice.Clinical Trial Registrationhttps://www.chictr.org.cn/bin/project/edit?pid=211769, identifier ChiCTR2400079391.